Pemberdayaan Usaha Kecil Menengah Masyarakat dalam Mendorong Pendapatan Daerah - Sri Ka’bah; Fandi Hi. Latief (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the empowerment of Small and Medium Enterprises in the Morotai community in encouraging regional income, as well as the factors that are considered to influence it. The method used in this study is a qualitative description in which a study that describes directly the facts found in the field. The methods used to collect data are, observation, interviews and documentation. After the data is completed, the researcher analyzes the data by reducing the data, presenting the data and drawing conclusions. There is no formulation and/or policy model in favor of the government for small business developers in Pulau Morotai Regency which is also followed by the difficulty of obtaining permits from various agencies for production and trade purposes, not only because of the cost, but also the centralized requirements (for example, having to follow the required upgrading process). held only in the district capital). For this reason, there needs to be a synergy between supporting elements, both the government, the private sector and the community. This was followed by the development of the quality of human resources for industrial business actors, empowerment programs, and the provision of supporting facilities for the development of MSMEs in Morotai Island Regency.